2011
DOI: 10.1016/j.automatica.2010.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Minimal single linear functional observers for linear systems

Abstract: A constructive procedure to design a single linear functional observer for a time-invariant linear system is given. The proposed procedure is simple and is not based on the solution of a Sylvester equation or on the use of canonical state space forms. Both stable observers or fixed poles observers problems are considered for minimality.(I. Zambettakis).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 23 publications
0
33
0
Order By: Relevance
“…It can be concluded that Conditions III and IV together are the necessary and sufficient conditions for the existence of an asymptotic UIFO with structure (2), and of order l for the system (14). Moreover, for the aim of the present paper, which is designing a proper UIFO, it can be shown that Conditions IV and II are identical.…”
Section: Remark 10mentioning
confidence: 73%
See 1 more Smart Citation
“…It can be concluded that Conditions III and IV together are the necessary and sufficient conditions for the existence of an asymptotic UIFO with structure (2), and of order l for the system (14). Moreover, for the aim of the present paper, which is designing a proper UIFO, it can be shown that Conditions IV and II are identical.…”
Section: Remark 10mentioning
confidence: 73%
“…Functional observers are a generalized version of ordinary fullorder or reduced-order Luenberger observers that are aimed at reconstructing a single or multiple functions of the states of the system [12][13][14][15]. This class of estimators has superiority in giving observers with lower order than the ordinary reduced-order observers.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has allowed to propose stable Luenberger observers with minimal order to estimate a linear form of the state in [24]. It has been shown there that increasing index ν in the fundamental relation (5) allows to design a stable observer for which more and more poles can be fixed.…”
Section: Single Linear Functional Observermentioning
confidence: 99%
“…However, those conditions are for the minimum order functional observer, i.e the order equal to the number of functions to be estimated. In many cases when these conditions are not satisfied, it is still possible to increase the order of the observer in order to design a stable functional observer for the system ( [20], [21], [22]). For such cases, two interesting questions would be as follows: 1) when is it possible to design a functional observer by increasing its order, and 2) how to design a functional observer with the minimum possible order.…”
Section: Introductionmentioning
confidence: 99%